Unilateral T-shaped incomplete duplex nephrectomy in an adolescent under laparoscopy: A case report. Issue 12 (26th March 2021) - He, HuaJie; Huang, YuanBi; Yu, Lu; Li, QiGuang; Long, Xian; Li, YongPeng; Chen, RongChao; Yi, XianLin
Abstract: Introduction: Duplicate kidneys are the most common congenital abnormality of the urinary system. The location of duplicate kidneys varies. We report a case of an adolescent with upper and lower kidneys that are arranged vertically and approximately T-shaped. Patient concerns: A 16-year-old male teenager was examined for pain in the left side of the waist. The Computed Tomography scan revealed that the left kidney was incompletely duplicated and fused; the left upper urinary tract was incompletely obstructed. Diagnosis: The abdominal tomography confirmed the diagnosis of incomplete duplicate kidney. Interventions: The patient underwent laparoscopic surgery. The failure to ligate the renal pedicle resulted in increased bleeding during the operation and an open ureteral stump. Outcomes: No urine leakage occurred after the operation. Doppler ultrasound of the urinary system showed no hydronephrosis, and the patient was asymptomatic. Conclusion: Through this case report, we found that the duplicate kidneys could be arranged in a T-shape under laparoscopy. Although only the supply of the duplicate renal arteries can be ligated during surgical resection, the renal pedicle must also be ligated during the operation if there is a lot of bleeding.